(3GdeNJGQ ef TYQ CHj aQGS GdMeOGfjs - (3eLghds; (3CHh aQGS , GdMGQK Hf SYjO Hf MeOGf GdJZdHj GdQHYj, CHhaQGS GdMeOGfj,J (B357 (3g` s
(3ChdgG (B:s
(3GdTYQ OjhGf GdYQH CHOkG hYfhGf GdCOH de CoYO ajg eaGNQj heOjM CHGFj GdofoLH s
(3BNQgG (B:s
(3eHJhQ, hBNQ GdehLhO ajg(B: (3dg HGdgeGe GHf GdeYepQ aJcI haj GdSja ajgG hGdQeGM YhGOQ jMji CHhGdZWQja Ydj Hf MeOGf hcGf Ydi CSf hdO MeOGf hCTLYge, eGJ MOKkG hSGQ GHfg MJi cGf s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGdKs
(3HgG fXGe GdJYbjHIs
(3JHUQI GdYfhGf (B:s
(3GNJjGQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B156s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B6 - (3U (B30 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B773s
Keywords: (3GdCOHs